Head and neck virtual medicine in a pandemic era: Lessons from COVID‐19. Issue 6 (22nd April 2020) - Prasad, Aman; Carey, Ryan M.; Rajasekaran, Karthik
Abstract: The 2019 novel coronavirus disease (COVID‐19) has presented the world and physicians with a unique public health challenge. In light of its high transmissibility and large burden on the health care system, many hospitals and practices have opted to cancel elective surgeries in order to mobilize resources, ration personal protective equipment and guard patients from the virus. Head and neck cancer physicians are particularly affected by these changes given their scope of practice, complex patient population, and interventional focus. In this viewpoint, we discuss some of the many challenges faced by head and neck surgeons in this climate. Additionally, we outline the utility of telemedicine as a potential strategy for allowing physicians to maintain an effective continuum of care.